Effect of Composite Flour Proportions (Mocaf, Pedada Fruit, Soybean) and GMS (Glycerol Monostearate) Addition on the Characteristics of Analog Rice - Reni Dwi Anggraini; Jariyah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Analogue rice is an artificial rice made from carbohydrate sources, both in form and nutritional composition that are almost similar to rice. This study utilised flour (mocaf, pedada fruit, soybean) as raw materials due to their limited availability. The addition of GMS functions as a stabiliser and emulsifier during extrusion, making the extrudate non-sticky, improving physical properties and texture, reducing the occurrence of excessive extrudate development, and improving the shape of the final product of analogue rice after the hydration process. This study aims to analyse the effect of composite flour proportions (mocaf, pedada fruit, soybean) and GMS (Glyserol Monostearate) addition on the characteristics of analogue rice, and to obtain the best treatment of analogue rice with product characteristics preferred by panellists. The study was arranged by using a Completely Randomized Design (CRD) with two factors and two replications. Factor I, namely the flour proportions (mocaf, pedada fruit, soybeans) consisting of (75:5:20; 70:10:20; 65:15:20), while factor II was the addition of GMS (1%, 2%, 3%). The best treatment results were obtained at the proportions of flour (mocaf, pedada fruit, soybean) (75:5:20) with the addition of 1% GMS resulting in a water content of 4.96%, ash content of 1.55%, fat content of 3.08%, protein content of 8.45%, carbohydrate content of 81.96%, starch content of 66.34%, amylose content of 20.24%, rehydration power of 124.02%, and expansion volume of 145.80%. Contribution to Sustainable Development Goals (SDGs):SDG 2 (Zero Hunger)SDG 12 (Responsible Consumption and Production)SDG 9 (Industry, Innovation, and Infrastructure).